Study of Comparing Combined Viscocanalostomy - Trabeculectomy to Trabeculectomy for the Management of Glaucoma - Verma, Dr. Anand; Kaushal, Dr. Pratibha (International Journal of Innovative Research in Medical Science, 2018)
Purpose: To compare combined viscocanalostomy - trabeculectomy to trabeculectomy in Primary Open angle glaucoma. Material and Methods: A total of 20 patients (40 eyes) of bilateral Primary Open Angle Glaucoma (POAG) were included in this study. They were randomly divided into two groups. Twenty eyes underwent combined viscocanalostomy - trabeculectomy and other twenty eyes underwent trabeculectomy with releasable suture. Combined viscocanalostomy - trabeculectomy constituted lamellar sclera flap, deep sclera flap dissection, excision of deep sclera flap, deroofing of sclemn’s canal, viscodilatation of sclemn’s canal, trabeculectomy and tight flap closure. Success criteria included intraocular pressure < 14 mmHg or more than 30% reduction of IOP. Result: Although in both the groups IOP was decreased, there was more lowering of IOP in combined viscocanalostomy -trabeculectomy than trabeculectomy. Target IOP was achieved in 95 % in viscocanalostomy - trabeculectomy group compared to 85% in trabeculectomy group.